2017
DOI: 10.1002/jocc.12059
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Dialectical Behavior Therapy for College Counseling Centers

Abstract: College counseling centers report increased student presentation with severe psychological issues (Gallagher, 2012). Although dialectical behavior therapy (DBT) has demonstrated efficacy with multiple clinical populations, standard model DBT is not feasible for many traditional college counseling centers. This article describes the iterative development and evolution of a comprehensive DBT program adapted to fit the scope of a traditional college counseling center. Guidelines for implementing lessons learned o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In a meta‐analysis, Lenz et al () found that DBT may be efficacious in reducing the number of disordered eating episodes as well as decreasing comorbid depression. DBT addresses four areas of skill development: mindfulness, distress tolerance, interpersonal effectiveness, and emotion regulation (Chugani, ; Lenz et al, ). Chugani () offers suggestions for implementing DBT in a college counseling setting.…”
Section: Implications For College Counselingmentioning
confidence: 99%
See 2 more Smart Citations
“…In a meta‐analysis, Lenz et al () found that DBT may be efficacious in reducing the number of disordered eating episodes as well as decreasing comorbid depression. DBT addresses four areas of skill development: mindfulness, distress tolerance, interpersonal effectiveness, and emotion regulation (Chugani, ; Lenz et al, ). Chugani () offers suggestions for implementing DBT in a college counseling setting.…”
Section: Implications For College Counselingmentioning
confidence: 99%
“…DBT addresses four areas of skill development: mindfulness, distress tolerance, interpersonal effectiveness, and emotion regulation (Chugani, ; Lenz et al, ). Chugani () offers suggestions for implementing DBT in a college counseling setting.…”
Section: Implications For College Counselingmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, many barriers exist against implementing a comprehensive DBT treatment in limited resource settings such as UCCs due to the scope of clinical services, heterogeneity of presenting concerns, productivity demands, and practical barriers to treatment fidelity (Chugani & Landes, 2016). Thus, Chugani (2015Chugani ( , 2017 suggested that adapted, time-limited DBT skills training group therapy can be an evidence-based treatment module that can easily fit the needs, demands, and limitations of UCCs and effectively treat students with vulnerability to severe and complex mental disorders. This suggestion is in line with Valentine et al (2015) who systemically reviewed 17 clinical trials and presented preliminary evidence of the utility of DBT skills training as a stand-alone treatment.…”
Section: Introductionmentioning
confidence: 99%